Vestibular Aqueduct Morphology and Meniere's Disease—Development of the “Vestibular Aqueduct Score” by 3D Analysis - Noyalet, Laurent; Ilgen, Lukas; Bürklein, Miriam; Shehata-Dieler, Wafaa; Taeger, Johannes; Hagen, Rudolf; Neun, Tilmann; Zabler, Simon; Althoff, Daniel; Rak, Kristen (Frontiers in Surgery, 2022)
Improved radiological examinations with newly developed 3D models may increase understanding of Meniere’s disease (MD). The morphology and course of the vestibular aqueduct (VA) in the temporal bone might be related to the severity of MD. The presented study explored if the VA of MD and non-MD patients can be grouped relative to its angle to the semicircular canals (SCC) and length using a 3D model. Scans of temporal bone specimens (TBS) were performed using micro-CT and micro flat panel volume computed tomography (mfpVCT). Furthermore, scans were carried out in patients and TBS by computed tomography (CT). The angle between the VA and the three SCC, as well as the length of the VA were measured. From these data, a 3D model was constructed to develop the vestibular aqueduct score (VAS). Using different imaging modalities it was demonstrated that angle measurements of the VA are reliable and can be effectively used for detailed diagnostic investigation. To test the clinical relevance, the VAS was applied on MD and on non-MD patients. Length and angle values from MD patients differed from non-MD patients. The angle of the lateral SCC showed the highest deviation in MD patients. In MD patients, significantly higher numbers of VAs could be assigned to a distinct group of the VAS. In addition it was tested, whether the outcome of a treatment option for MD can be correlated to the VAS.